Accounting Polices, Changes in Accounting Polices, Errors, Changes in Estimates Accounting and Accounting and Operations Discontinued by Tapin District Government - Irene Yovalina Emeninta br Bangun; Naomi Meyriza br Tarigan; Iskandar Muda (CV. Kalimasada Group, 2025)
This study examines the implementation of accounting policies, policy changes, error corrections, changes in estimates, as well as the accounting treatment of discontinued operations in the Tapin Regency Government. Based on PP No. 71/2010 on SAP, this study analyzes how accrual-based accounting shapes local financial reporting practices through a qualitative literature review approach that includes regulations, audit reports, and academic studies. Results show that Tapin has generally implemented SAP consistently since the adoption of accrual accounting in 2015. However, challenges remain in asset classification, effectiveness of internal controls, and accuracy of accounting estimates. Error correction is still affected by limited technical capacity, while policy changes require retrospective application to maintain comparability. Reporting discontinued operations improves transparency, but also reflects the region's vulnerability to sectoral shocks. Overall, this study emphasizes the importance of strengthening internal controls, digital integration, improving HR competencies, and better disclosure practices to support accountable and transparent local financial governance.